Efficacy and safety of risperidone oral solution in agitation associated with dementia in the elderly - Jerson Laks; Eliasz Engelhardt; Valeska Marinho; Marcia Rozenthal; Fernando de Castro e Souza; Josué Bacaltchuk; Alberto Stoppe Jr.; R.C.R. Ferreira; Cassio Bottino; Mônica Scalco (Arquivos de Neuro-Psiquiatria)
BACKGROUND: Behavioral and psychological symptoms in dementia (BPSD) contribute to caregiver burden and institutionalization of elderly. Neuroleptics are prescribed to control agitation. Side effects of typical neuroleptics are harmful, making atypical neuroleptics an indication. OBJECTIVES: To evaluate efficacy and tolerability of risperidone oral solution (ROS) given once daily to demented elderly outpatients with BPSD (agitation). METHOD: Patients (n=26), 76.35±8.63 years, Diagnostic and Statistical Manual of Mental Disorders 4th ed. (DSM-IV) criteria for dementia. RSO was given, starting dose of 0.25 mg and increments of 0.25 mg every week. Mini-Mental State Examination (MMSE) assessed cognitive status, Behavioral and Emotional Activities Manifested in Dementia (BEAM-D) and Clinical Global Impression (CGI) measured BPSD, Extrapiramidal Symptom Rating Scale (ESRS) evaluated extrapyramidal symptoms. Cardiovascular side effects were evaluated clinically. RESULTS: There was a 26% reduction in agitation and no cardiovascular side effects in the range from 1.0 to 1.25 mg. Side effects were more prevalent above 2.5 mg. CONCLUSION: Risperidone oral solution improved agitation with good tolerability from 0.5 to 1.25 mg. A single dose with increments of 0.25 mg may be more acceptable to patients and caregivers.